DNA Catalysis of a Normally Disfavored RNA Hydrolysis Reaction - Parker, Darren J. (2013)
We recently used in vitro selection to identify many deoxyribozymes that catalyze DNA phosphodiester bond hydrolysis and create 5′-phosphate and 3′-hydroxyl termini. Alternatively, numerous deoxyribozymes have been identified for catalysis of RNA cleavage by 2′-hydroxyl transesterification, forming 2′,3′-cyclic phosphate and 5′-hydroxyl termini. In this study, we investigated the ability of DNA to catalyze RNA cleavage by hydrolysis rather than transesterification, although normally the hydrolysis reaction is substantially disfavored relative to transesterification. Via a series of in vitro selection experiments, we found that reselection of a DNA-hydrolyzing deoxyribozyme leads either to transesterification or hydrolysis, depending on exclusion or inclusion of a stringent selection pressure for hydrolysis. An entirely new selection starting from a random DNA pool, using an all-RNA substrate and imposing the same selection pressure, also leads to RNA hydrolysis. Collectively, these results establish experimentally that small DNA sequences have the catalytic ability to direct a chemical reaction down a disfavored pathway, even when a more favorable mechanism is readily available. Our view of DNA catalysis is therefore expanded beyond merely increasing the rates of reactions that would have occurred more slowly without the catalyst.